Outage probability analysis of overlay cognitive two‐way relaying scheme with opportunistic relay selection. Issue 5 (10th March 2021) - Ma, Long; Li, Enyu; Wang, Xinjie; Gu, Meng; Yang, Qianqian
Abstract: The authors investigate an overlay cognitive two‐way relaying system where max‐min (MM) relay selection scheme is employed for improving the reliability of the considered system. Furthermore, they design the process of the data forwarding and relay selection in the overlay cognitive two‐way relaying system. Based on the MM relay selection criterion, the exact close‐form expression of outage probability is derived. From numerical simulations, it is observed that there is an outage probability floor appearing in the high signal‐to‐noise ratio (SNR) region, and the reason for its occurrence is stated. Besides, the approximate result of outage probability in high SNR is provided, which shows that the ratio of interference channel' transmit power and main channel' transmit power will not affect the outage probability in low SNR region, but it will significantly affect it in the high SNR region. Although each individual channel state information (CSI) will not be able to control the outage performance of this considered system in the high SNR region, the ratio of each channel's CSI will be able to do the same.